Slave patrols : law and violence in Virginia and the Carolinas - Hadden, Sally E. (Harvard historical studies, 2001)
Hadden examines the patrols, the most frequent enforcers of the laws involving slaves, and how they influenced race relations and the Ku Klux Klan after the Civil War.